Developement of the activity of the reform movement in Tlemcen (1932-1956) Ecole Dar El Hadith-Modèle - tabti, hayet (Journal of Social Sciences and Humanities, 2020)
The Algerian Muslim scholars association has made a great step in the early of thirties of the twentieth century, in the field of education and teaching in Arabic, the association tried to open, free schools in Algerian cities through the formation of local reform associations from people who believed in the principles of the association, In spite of all the difficulties, the Arab schools have grown and developed by the Society. Among these cities, which attracted the attention of the Association of Scholars, the city of Tlemcen, which has been considered a destination for scholars and thinkers since ancient times, And the selection of Sheikh El Ibrahimi supervision of the western area taking Tlemcen based, and the appearance of El Ibrahimi in Tlemcen significant impact in the construction of “Dar Al-Hadith” where he was the main engine of the process of construction and finance. The purpose of the “Dar Al Hadith” was to revive the Arab culture and to resist French educational policy. This school was opened in the presence of a large group of scholars and residents of Tlemcen. It was founded thanks to the efforts of the Imams Ibn Badis and El Ibrahimi, and the Algerian press was interested to this event, But the joy did not last long where the French administration closed the sections dedicated to education, but the lecture hall and the mosque remained standing, and after disabling immediately,Sheikh Ibn Badis sent a letter to the administration, in which he stressed the need to interest the authority to demand the Tlemcenians of opening the school. Sheikh El Ibrahimi also did not accept this decision and challenged the French administration after the closure of the school, by refusing to sign the minutes of the order to close the school, did not surrender the imam to continue his activities continued to work, and this school was an important position of Imam Ibn Badis, He mentions it in public speeches and private councils. The activity of Sheikh El Ibrahimi in Tlemcen before the Second World War in the school was varied and important, and people were flocking to it from the east of Algeria and the center and west, but at the beginning of the war the school was closed again, and not only El Ibrahimi activity on Tlemcen alone, But he included all the western side, he visited the cities and villages, and gave lessons and lectures, calling for the establishment of mosques, and the construction of schools, and the establishment of clubs and the formation of associations to promote cooperation between people, as the school is only the scientific side and the Arabic language and the Koran But it also had a section devoted to various cultural activities such as It was one of the best measures taken by the Association of Scholars for its Arab Islamic schools, its decision to conduct annual exams for its students who completed their elementary education. The Education Committee decided to conduct this exam in certain centers in the three currencies by three committees, Dar al-Hadith. This school played an important role in spreading and defending free Arab education, on the other hand in the Algerian national movement, as well as in the liberation revolution. The mission of the association was not easy, but it was full of difficulties encountered by the French administration.